THE EFFECTS OF WORK COMPETENCE, WORK MOTIVATION AND INTELLECTUAL EMPLOYEE INTELLIGENCE ON EMPLOYEE PERFORMANCE WITH THE WORK ENVIRONMENT AS A MODERATION VARIABLE AT BAPPEDA SLEMAN REGENCY - Sugianto; Maimun Sholeh (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The Effect of Work Competencies, Work Motivation and Intellectual Intelligence on Employee Performance with Work Environment as a Moderation Variable at BAPPEDA Sleman Regency. This study aims to analyze the influence of motivational competence and intellectual intelligence on employee performance in BAPPEDA Sleman Regency with the work environment as a moderation variable. This research is a quantitative research using SEM-PLS. The results of the study shows that work competence has a positive and significant effect on employee performance, work motivation does not affect employee performance, intellectualintelligence has a positive and significant effect on employee performance, work environment has no effect on employee performance, work environment US a moderation variable cannot moderate the influence of work competence on employee performance, work environment as a moderation variable cannot moderate the Influence on the Influence of Intellectual Intelligence on Employee Performance, the Work Environment as a Moderation Variable cannot moderate the Influence of Work Motivation on Employee Performance